Expression and characterization of functional HIV-1 subtype C envelope glycoproteins in insect cells. - Nkosi., Praise-God Sibusiso. (My University, 2002)
The full-length envelope glycoproteins from four South African HIV-1 subtype C isolates exhibiting different phenotypic properties were expressed in insect cells, purified, and their biological characteristics investigated. Isolates 98ZA151Du, 99ZACM9, 98ZA179DU and 99ZASW7 that utilize the CCR5, CCR5/CXCR4, CCR5/CXCR4 and CXCR4 coreceptors for cell entry, respectively were selected for this study. All four full-length env genes were PCR amplified, cloned into a baculovirus expression system and the recombinant envelope glycoproteins were expressed in Spodoptera frugiperda (Sf9) insect cells.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, for the degree of Masters of Science in Medicine (Virology). Johannesburg, 2002
Keywords: Glycoproteins; HIV-1; Spodoptera